Penerapan Aspek Bioetika dalam Penggunaan Pestisida Nabati terhadap Pencegahan Hama Lingkungan: Studi Kasus di UPT Pengembangan Benih Hortikultura Dinas Ketahanan Pangan Pertanian dan Perikanan Kota Medan - Bunga Ria Sitanggang; Nur Afliza; Rika Lidia Sibarani; Ahmad Shafwan Pulungan; Nurbaity Situmorang (Lembaga Pengembangan Kinerja Dosen, 2025)
The study explores the application of bioethical aspects in the use of botanical pesticides for pest prevention in the environment at the Horticultural Seed Development Unit (UPT) under the Department of Agriculture and Fisheries. Utilizing a qualitative approach with quantitative elements, this research aims to deepen understanding regarding bioethical practices in botanical pesticide usage and evaluate its effectiveness in controlling pests. The population consists of employees and students involved in pesticide-related activities, selected through purposive sampling to ensure knowledgeable respondents. Key variables include the independent variable of botanical pesticide application and dependent variables such as pest population reduction, environmental impact, and the presence of beneficial non-target organisms like pollinators. The descriptive qualitative method combined with survey techniques provides insights into how bioethical principles are integrated into pest control strategies, promoting sustainable agricultural practices. This research contributes to advancing environmentally friendly pest management solutions while maintaining ecological balance.